Cognitive apprenticeship and structured debriefing as tools to develop reflective practice in initial teacher education - Moya, Mario Raúl (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This article discusses the use of reflection in the development of pre-service teachers’ skills in school placements, as utilised in a Teacher Training College in Bedford, England, following the views of Schön (1987), Dewey (1988), and Eraut (1994) in relation to the use of reflection to inquire into teaching practice. Such reflective process is facilitated by the model of cognitive apprenticeship (Collins, Brown & Newman, 1989) and by the technique of structured debriefing (Gibbs, 1988) for the identification of areas for improvement, the implementation of interventions, and the assessment of outcomes. The use of reflection enables teaching to be reinterpreted as a critical practice with the potential to produce transformative learning whilst also promoting communities of practice based on inquiry and action research.